Molecular approach challenges the monophyly of the genus Benthana Budde-Lund, 1908 (Oniscidea, Philosciidae) - Zimmermann, Bianca Laís; Soares Campos-Filho, Ivanklin; de Araujo, Paula Beatriz; Bartholomei-Santos, Marlise L.; Santos, Sandro (Studies on neotropical fauna and environment, 2025)
Although new data and methodologies are gaining prominence in the field of taxonomy, the vast majority of terrestrial isopod species are still described solely based on morphology. The genus Benthana was recently revised and currently comprises 30 species found in South America. However, the broad geographic distribution of some species, coupled with the presence of few diagnostic characters, raises doubts about the validity of the described species. This study aimed to test the applicability of DNA Barcoding to assess the congruence between morphological and molecular identification of Benthana species. We analyzed 72 individuals belonging to 13 species from the scientific collection of the UFRGS Crustacean Laboratory. We obtained 24 sequences from ten Benthana species. The molecular phylogenies demonstrated that Benthana forms a paraphyletic group. Even at the species level, paraphyletic taxa were observed. Species delimitation methods revealed the presence of eight molecular entities within Benthana. Regarding genetic distances, we observed low intra-specific distances and significantly high inter-specific distances. Our results show that molecular analysis does not support the current taxonomy of Benthana. Therefore, a reassessment of the genus systematics based on integrative taxonomy is warranted.